Lack of association between loneliness, social isolation and inflammation in people living with HIV aged ≥50 years: Results from the sub-study “No One Alone-Gesida Study” - Jose-Ramon Blanco; Helena Albendín-Iglesias; Eugenia Negredo-Puigmal; Ana Mª Barrios-Blandino; Cristina Tomás-Jimenez; Isabel Sanjoaquin-Conde; María Saumoy; Verónica Pérez-Esquerdo; Inmaculada Gonzalez-Cuello; Ana María López-Lirola; Maria José Galindo; Noemi Cabello-Clotet; et al. (PLoS ONE, 2025)
Introduction Inflammation is linked to multiple health conditions. Emerging evidence suggest it may play a role in the association between social isolation – loneliness and health outcomes. People living with HIV (PLWH) exhibit chronic inflammation even with viral suppression, likely due to ongoing immune activation. However, few studies have explored inflammatory biomarker in PLWH experiencing loneliness or social isolation. This study aimed to assess this association in PLWH aged 50 or older.